The Development of Green Science Board Game (Greecebome) Media on Environmental Pollution toward Student Interest in Learning - Putri, Devita Roesikusuma; Ngabekti, Sri (Journal of Environmental and Science Education, 2021)
This study developed and analyzed Greecebome's feasibility as a learning media and to know also analyze the influence toward interest in learning of students. The type of this research is Sugiyono's research and development. The subject of this research is eleven students from junior high school. The data collection methods are observation and questionnaires. The results showed an average percentage of media feasibility by a media expert is 91%. A very decent category and average media feasibility percentage by a material expert is 88.75%, with very decent categories. Greecebome media is stated to be very well worth use in research after revisions according to the validator's suggestion. The interest in learning assessment from eleven students shows 94% with the category of interest in learning is very high. The assessment results from three science teachers show 96,88% with a very good category. From the assessment results, it can be concluded that Greecebome media is learning media that is very decent to support learning activities in class on environmental pollution material and encourage student interest in learning.